The relations between phenolic compounds and seed dormancy in Pistacia spp. - Isfendiyaroglu M.; Ozeker E. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
Seeds were collected from trees of Pistacia atlantica, P. terebinthus and a hybrid, with unknown parents. They were sown in petri dishes for determining the germination percentage and mean time to complete germination (MTG) either without stratification or pretreated with 1000 ppm gibberellic acid (GA3). The rest of the seeds were stratified in moist perlite at +4 degrees C. The stratification was interrupted in days 15, 30 and 45, then seeds were sown. MTG of seeds pretreated with GA3 and stratified were higher than the controls in all species. The germination percentage of P. atlantica was higher than in the other species. The phenolic compounds were analysed by using the Thin Layer Chromatography method to determine their effects on seed dormancy. Generally, concentrations of phenolics varied with GA3 and stratification treatments. As a result of examining two dimensional chromatograms, the highest number of phenolics were observed in P. atlantica.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)